Pain Relief as a Primary Treatment Goal: at What Point does Functioning and Well-Being Become more Important? a Case Study of an Adolescent with Debilitating Chronic Pain - Andrew S Tseng; Karen Weiss; Tracy Harrison; Dan Hansen; Barbara Bruce (Pain Research and Management)
BACKGROUND: Pediatric chronic pain is a common problem with significant economic implications and devastating consequences on quality of life. The present report describes a case involving a 15-year-old girl with severe and debilitating chronic pain.